The new security grey zone: export controls, emerging technologies and US-China technological rivalry. - Schneider Rasador, Guilherme; Moreira Cunha, André (Pacific Review, 2025)
The contemporary use of export controls by the US as a tool for compliance and enforcement has expanded a grey zone within global economic networks, where security and economic measures increasingly justify one another. These export controls, combined with industrial policies, reflect an emerging geoeconomic strategy. We examine the US growing use of export controls as a geoeconomic tool to curb China's technological advancement, particularly in the semiconductor industry, focusing on the active role of the Bureau of Industry and Security (BIS). We argue that the BIS has significantly expanded its influence under the Trump and Biden administrations, especially through policies targeting US-China technological rivalry, such as the Foreign Direct Product Rule (FDPR). This expansion is analysed through the lens of extraterritoriality, emphasising the usage of US structural power within the semiconductor industry and its supply chains. We illustrate how these policies reflect a new geoeconomic order, where economic interdependence is weaponised for strategic objectives, and global supply chains become arenas of geopolitical competition. By blocking China's access to critical technologies, these policies reinforce US leadership but risk leading to long-term geoeconomic fragmentation in global trade and investment, raising relevant questions about international economic governance.